Studi Kasus: Foot Rot pada Sapi Perah di KUD Dadi Jaya Purwodadi Pasuruan Jawa Timur - Wicaksono, Naura Rahmi (VITEK : Bidang Kedokteran Hewan, 2023)
Foot rot is a sub-acute or acute necrotic (decaying) infectious disease of cattle, causing swelling and lameness in at least one foot. A dairy cattle named Jessica was reported to KUD Dadi Jaya Purwodadi Pasuruan, suffering from a loss of appetite, had a wound on the heel area of the right hind leg, reddish and broken skin, with a foul odor. The wound has been going on about 6 days and has been treated by veterinary using antibiotics and anti-inflammatories, five days ago. Jessica has a tendency to have too-long nails, which makes her posture lame. Physical examination revealed that Jessica could still stand well, but she didn't move around much with wound in the interdigital area of her right hind leg. Her body temperature was still normal. The treatment includes intramuscular injections of Oxytetracyline 200 mg (Medoxy-LA®) as an antibiotic, Tolfenamic acid 80 mg (Tolfen-LA®) as an anti-inflammatory and analgesic, as much as 15 ml, and Life-Vit® 10 ml as a therapy supportive, which were all prescribed. The next step involves applying a topical medication to the wound using Limoxin-25 Spray, which contains 250 mg of Oxytetracycline.